Analysis of Differences in Timeliness of Providing Outpatient Medical Record Documents in the Terminal Digit Filling Filing System at Hospital - Ikhwan Ikhwan; Musparlin Halid (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2022)
Filling a system document of the medical record is a system of using to arrange a bundle of the medical record in share of filing. The research intends to analyze different time rapidity of supplying the Medical Record Document (MRD) manner take care of the filing system of Terminal Digit Filing (TDF) and the Straight Numerical Filing (SNF). This research was an analytic observational study with a cross-sectional approach by analyzing the difference in the timeliness of providing outpatient medical record documents to the TDF system at Patut Patuh Patju (Tripat) Hospital and SNF at Siti Hajar Mataram Hospital. The study was conducted from January to May 2022. The study population was old patients taken care of in the Tripat Hospital and Siti Hajar Mataram Hospital. The research sample was 90 MRDs in the Tripat Hospital and 87 MRDs in the Siti Hajar Mataram Hospital taken with systematic random sampling. The instrument used an observation sheet and the time of providing MRD, both in the TDF and SNF systems. The data was quantitative data obtained from the speed of time for providing MRD. Analysis of research used experiment of Independent Sample t-test. The experiment statistic used the aid of the SPSS Version 20 software. The result of the study indicated different supplying time rapidly of documents of the medical record manner taking care of system juxtaposition of terminal digit filing and straight numerical filing (P-Value = 0,043).